Characterization of HDPE Waste-Bentonite Clay-Jute Fiber Composite Materials: Impact Strength and Density Analysis - Thoriq Bintang Fadillah; Kriswanto; Kaleb Priyanto; Immanuel Eltian Sudjana (Universitas Medan Area, 2026)
This study evaluates composite materials' impact strength and density from recycled high-density polyethylene (HDPE) waste reinforced with woven jute fibers and filled with bentonite clay at varying volume fractions (2%, 4%, 6%, and 8%). The composites were fabricated using a hot press molding technique. Density was measured following ASTM D792, while impact strength was assessed using the unnotched Charpy method based on ISO 179. Results showed that increasing bentonite content raised the composite's density due to the higher specific gravity of the clay. Impact strength exhibited a non-linear behavior, peaking at 4% bentonite with a 13.5% increase compared to the 2% variant. However, further increases in clay content led to a significant drop in impact strength, primarily due to filler agglomeration and reduced matrix-fiber interfacial bonding, which resulted in brittle fracture modes. Macro-photographic analysis of fracture surfaces confirmed this trend, revealing ductile failure, fiber pullout at low clay contents, and sharp, brittle fractures at higher contents. These findings highlight the importance of optimizing filler content to balance density and mechanical performance, offering insights for developing sustainable composite materials for structural and industrial applications. Keywords: recycled HDPE, natural fiber composite, bentonite clay, impact strength, density